The Experience of Grade V Elementary School Students in Writing Creative Stories Based on Storyscaping at SD Negeri Lanbau 01 - Fatma, Fatmawati; Helmanto, Fachri; Effane, Anne (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2025)
This study aims to describe the experiences of fifth grade elementary school students in writing creative stories based on storyscaping and identify the challenges faced in the process. The storyscaping approach integrates elements of visualization, exploration of personal experiences, and development of creativity to help students write stories with a systematic narrative structure. Data were obtained through in-depth interviews with students and documentation of their writing. The results showed that this method was effective in enhancing students' creativity, enabling them to think critically, generate original ideas, and understand and internalize moral values in the story. In addition, students showed an increase in interest and ability in writing stories, supported by a supportive learning environment and teacher guidance. This study also found that storyscaping-based story writing helped students recognize culture, strengthen self-identity, and increase awareness of environmental issues through relevant personal experiences. However, the main challenges include students' limitations in developing complex storylines and utilizing creative elements optimally. This study provides a new contribution to experiential learning by combining narrative and technology approaches to improve students' writing skills. This emphasizes the importance of innovation in education to support literacy competencies in the digital era.